Educação de Jovens e Adultos no ensino médio no Estado do Maranhão: o abandono e a evasão escolar em questão - PEREIRA, Diego Rodrigo (2024)
This study was carried out in the Postgraduate Program in Education at the Federal University of Maranhão, through the Research Group on Policies, Educational Management and Human Training, in the line of investigation History and Policies of Education, to explain the following problem: how Do school dropouts and dropouts materialize and are they addressed in Youth and Adult Education? The objective is to analyze dropout and dropout in Youth and Adult Education in High School and strategies to combat these phenomena in Maranhão. As methodological procedures, a qualitative approach, bibliographical, documentary and field research was used in sectors and schools linked to the State Department of Education of Maranhão, in which school managers, pedagogical coordinators, teachers, students and supervisors answered questionnaires and interviews. The research results showed that socioeconomic aspects are confirmed as crucial factors in abandonment and dropout in Youth and Adult Education in High School, as they directly interfere with the student's conditions of permanence and continuity at school. However, other factors are linked to these, such as the lack of physical and pedagogical support, reception and guarantee of rights from the government, local management and the school itself. It was concluded that to face these phenomena, it is necessary for governments and managers to commit to public policies aimed at reducing socioeconomic inequalities, enriching the quality of education, building and renovating schools, creating teacher training programs and the construction of the modality's curriculum based on differentiated practices that consider the identities and diversities of students, reconfiguring the school as an agency of reception and social transformation.